Assessment of Patient Satisfaction with Pharmaceutical Community Services in R. Macedonia - Zoran Sterjev; Bogdan Vlaco; Aleksandra Kapedanovska Nestorovska; Zorica Naumoska; Aleksandra Grozdanova; Ljubica Suturkova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2011)
Measuring and analyzing patients' satisfaction with pharmacist's consultation is a relatively new development which is enforced by the new demands of society. High number of variables, such as their state of health, socio-demographic variables (age, sex, and cultural level), characteristics of their healthcare provider (affective care, quantity of information, technical expertise, etc), or waiting time are related to patients' satisfaction. At present, in R.Macedonia, there are 834 community pharmacies, which accounts for pharmacy vs. population ratio of 1:2500. The pharmacies are situated in 8 different regions (the Vardar region, Pelagonia, North-East, South-West, Polog, East and South East). The present cross-sectional descriptive study based on interview data was carried out in order to ascertain patients' satisfaction from their experience with the cumulative quality of pharmaceutical services. A total of 651 patients of both sexes (59,3% male and 39,1% female) were included in the study. The results from our analysis showed the influence of different factors in the process of choosing pharmacy: distance, medicines price, well-stocked with medicines, professional advice by the employees in the pharmacy, hygiene in pharmacies, the privacy they offer, waiting time, possibility for private conversation with professionals.